Dogs’ recognition of human selfish and generous attitudes requires little but critical experience with people - Carballo Pozzo Ardizzi, Fabricio (2017)
There is some dispute regarding the role of experience in the development of dogs´ socio-cognitive abilities in their interaction with people. We sought to provide new evidence to this debate by comparing dogs with contrasting levels of experience with humans, in a task involving the discrimination of human generous and selfish attitudes. To this end, we compared the performance of adult family dogs against that of adult shelter dogs and puppies living in people´s homes. In training trials, the generous experimenter (G) signaled the bowl with food and allowed the dog to eat, whereas the selfish experimenter (S) also signaled the baited bowl, but she/he ate the food before the dog could have access to it. Then, subjects were allowed to freely choose between G and S in the choice test. The main finding was that adult subjects (both family and shelter dogs) developed a preference for G over S, but puppies did not. We conclude that the quality and/or quantity of everyday-contact with people did not affect the discrimination of human attitudes in the present protocol, but the amount of experience with people (in years) did matter. Finally, we discuss the relative role of domestication and ontogeny in the development of dogs´ socio-cognitive abilities.